PENYULUHAN DAN PERCONTOHAN PENGGUNAAN LIMBAH PLASTIK UNTUK MATERIAL BAHAN BANGUNAN DI LINGKUNGAN RPTRA, JAKARTA BARAT - Grace Kurniawati; Lisa Oksri Nelfia; Ade Okvianti Irlan; Indrawati Sumeru (Universitas Trisakti, 2019)
Construction is growing rapidly nowadays. Buildings, housing, industry/business centers and highways will require natural aggregates which are natural resources that cannot be renewed. Therefore, we need replacement materials able to replace these natural aggregate. The large amount of plastic waste in fields, based on existing data, causes environmental pollution through it can be reused and useful for building and road construction. Most of communities don’t even know the plastic waste processing technology that allow their use in the construction of house construction such as floors, walls, roofs, and hinges and also road construction with not heavy road loads. The purpose of this activity is to provide the knowledge to the people of RPTRA related to technology for the use of plastic waste for building materials and also road construction in the area in the RPTRA environment considering it is not a public road and hence, with not heavy vehicle. The method used is firstly observation and interview of several houses visited. Then activities about using different types of plastic waste as construction materials. Finally, evaluation of the progress of the project by conducting a survey to people who had met the criteria of being a member of the plastic waste program. The success of this program will be the people’s understanding and a significate growing of any highvalue plastic use as construction material. The benefit of this community service is to increase the knowledge and insight of the people of RPTRA, South Meruya, and West Jakarta City, related to environmentally friendly technologies such as plastic waste processing.